Edukasi Keseimbangan Foremilk dan Hindmilk ASI pada Ibu Menyusui - Suci Rahmani Nurita; Diah Novita Sari (Jurnal Abdimas Kesehatan (JAK), 2020)
The infant morbidity rate is the second indicator in determining the degree of child health. Based on Paninsari (2017) research in exclusive breastfeeding mothers regarding the balance of foremilk and hindmilk breast milk, the majority of mothers have less knowledge (73.8%), positive attitude (90.8%) and did not balance foremilk and hindmilk breast milk (90.8%). Lack of knowledge breastfeeding mothers about the balance of foremilk and hindmilk breast milk will cause the baby to get more foremilk so that the baby can have difficulty in digesting all the unbalanced lactose. Imbalance of foremilk and hindmilk breast milk can cause health problems in infants such as Babies often bloated, often spit up and fuss without cause, digestive disorders such as diarrhea, watery consistency, foul-smelling, green color and foamy of baby feces and the addition of baby's weight is not according to KMS. The education carried out targeted an increase in the knowledge of participants pre and post counseling with outcomes in the form of informative leaflets, reports on the results of activities and journal publications. The implementation method is divided into 3 stages: the preparation, implementation, monitoring and evaluation stages. The results of the pre and post questionnaire analysis showed that the median score of correct answers increased from 3.00 to 6.00. It can be concluded that there was an increase in the knowledge of education participants regarding the importance of the balance of foremilk and hindmilk breastmilk.